2019
DOI: 10.1155/2019/7282681
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum-Effect Relationship between UPLC Fingerprints and Antilung Cancer Effect of Si Jun Zi Tang

Abstract: Nowadays, an increasing number of patients are seriously affected by lung cancer. Si Jun Zi Tang (SJZ), a four-herb Chinese medicine formula first described approximately one thousand years ago, is often prescribed for cancer patients as a complementary therapy. But the research on the effective materials for treating cancer using SJZ was rarely reported. To solve this problem, we evaluate the inhibitory effect of 10 samples of SJZ from different origins on PC9 cells. Ultraperformance liquid chromatography (UP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Of course, we will verify this result further in both cell and animal experiments in vivo . Our study not only established the spectrum-effect relationship, but also quantitative analysis of the active components in YYTN compared to other traditional Chinese medicine spectrum-effect correlations [ 20 , 34 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Of course, we will verify this result further in both cell and animal experiments in vivo . Our study not only established the spectrum-effect relationship, but also quantitative analysis of the active components in YYTN compared to other traditional Chinese medicine spectrum-effect correlations [ 20 , 34 ].…”
Section: Discussionmentioning
confidence: 93%
“…For example, the main vasorelaxant components of rosemary have been found by using the chemical spectrum-effect relationship [ 19 ]. HPLC fingerprint and bioactivity verification were used to investigate the potential correlation between the chemical components and pharmaceutical effects [ 20 , 21 ]. It is a representative method to find the main active components in complex traditional Chinese herbal formulas based on the study of spectrum-activity relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research showed that Si Jun Zi Tang (SJZ) can inhibit tumour growth in LLC‐bearing mice 28 . Ginsenosides Ro and Rg1 were the two major active components of SJZ in inhibiting PC9 proliferation by spectrum‐effect relationship analysis 29 . This effect may be attributed to ginseng, the main herb in SJZ.…”
Section: Discussionmentioning
confidence: 96%
“…e spectrum-activity relationship explores the relevance between the fingerprint and pharmacodynamics to offer a credible method for clarifying the material base of Chinese herbal medicine [21]. e fingerprints were established by HPLC, UPLC, GC, GC-MS, and LC-MS usually [19,[22][23][24]. "Pharmacodynamics" data is acquired by the biomodels usually [25].…”
Section: Introductionmentioning
confidence: 99%